Characteristics and impacts of itch in children with inflammatory skin disorders. (29th November 2020) - Fang, M.M.; Nowinski, C.J.; Lai, J.; Shaunfield, S.; Silverberg, J.I.; Rangel, S.M.; Cella, D.; Paller, A.S.
Summary: Background: Itch is a cardinal feature of paediatric disorders and can impair quality of life. However, few studies have addressed symptoms and impacts of itch in paediatric patients. Objectives: We focused on understanding the child's experience of itch and the impact of itch specifically on affected children, including comparison with the adult experience. Methods: Semistructured interviews (nine parents, 15 children with itch) explored concerns related to paediatric itch experiences and effects. Themes were compared with those of previous adult interviews. Literature was reviewed to identify the need for a more comprehensive measure of paediatric itch. Results: Itch quality, intensity, duration and environmental triggers (sweating, climate change, stress and certain fabrics) are important aspects of the child's itch experience. Skin disruption, physical function, concentration, emotional reactions, stigma and relationships/social effects are itch impact themes that emerged. No paediatric‐specific scale comprehensively captures the paediatric patient itch experience. However, differences between child and adult reports of itch‐related pain, functional limitations, fatigue and restlessness, emotional reactions to itch, and treatment effects emphasize the need for a paediatric‐specific measurement tool. Conclusions: Children and parents endorse the importance of capturing the paediatric‐focused characteristics and impacts of itch in measuring disease severity and response to intervention. Abstract : What is already known about this topic? Most children with pruritic disorders in the clinic or in clinical trials are asked a single question about itch intensity, if asked at all. However, the many negative impacts of itch in paediatric patients with atopic dermatitis and other pruritic disorders have not been well characterized and may differ from those in adults with pruritic disorders. What does this study add? Itch quality, duration and triggers are important itch characteristics, in addition to itch intensity, in understanding the itch experience and managing itch. While itch can lead to physical manifestations, such as excoriations and a risk of cutaneous infection, other important impacts include reduced physical function and ability to concentrate, disruption of social relationships, and increased stigma and emotional reactions. What are the clinical implications of this work? To comprehensively understand itch, practitioners should ask questions about itch‐related impacts on physical, mental and emotional health. An instrument that quickly assesses severity of itch symptoms and itch impacts in clinical practice is needed and can be based on the conceptual framework generated in this qualitative study. Given the differences between the itch experience in adults and children, a paediatric‐specific tool should be developed. Linked Comment: Zigler and Roberts. Br J Dermatol 2021; 184 :795–796 .